Worldwide revision of the genus Fraseroscyphus Boero and Bouillon, 1993 (Cnidaria: Hydrozoa): an integrative approach to establish new generic diagnoses - Song, Xikun; Xiao, Zefeng; Gravili, Cinzia; Ruthensteiner, Bernhard; Mackenzie, Melanie; Wang, Shaoqing; Chen, Jinjing; Yu, Nan; Wang, Jianjun (Zootaxa, 2016)
The morphological character of the hydrocladium and gonotheca origin from within the hydrothecal cavity has rarely been applied for generic diagnoses in hydrozoans. Its taxonomic value has been controversial for more than a century. The genus Fraseroscyphus Boero and Bouillon, 1993 (Hydrozoa: Sertulariidae) is a relatively recently debated case and it has been distinguished from Symplectoscyphus Marktanner-Turneretscher, 1890 based on this character. A review of this character in all published nominal species of the family Sertulariidae reveals that its occurrence is inconsistent at the genus level. However, phylogenetic analyses based on mitochondrial (16S) and nuclear (18S, 28S) genes support the position of Fraseroscyphus as a genus within the family Symplectoscyphidae Maronna et al., 2016. Comparisons of 16 morphological characters of 10 related species support the distinction of Fraseroscyphus from Antarctoscyphus and Symplectoscyphus by other characters in addition to the hydrocladial and gonothecal origin character. These new characters include the rarely-branched hydrocaulus, the absence of an apophysis, and the absence of an axillary hydrotheca. Furthermore, a revision based on the morphological character complex mentioned above using type and topotypic material, demonstrated that Sertularella sinuosa Fraser, 1948 (type species of Fraseroscyphus) and Symplectoscyphus huanghaiensis Tang & Huang, 1986 are junior synonyms of F. hozawai (Stechow, 1931) comb. nov. The assignment of Sertularella irregularis Trebilcock, 1928 and Sertularella macrogona Trebilcock, 1928 to Fraseroscyphus is also supported. In addition, sequence polymorphism of mitochondrial genes even within a single hydroid fragment was detected by the molecular cloning method, and is probably in part attributable to errors introduced by PCR, mitochondrial heteroplasmy and/or nuclear mitochondrial DNA (NUMTs). The adoption of the cloning method may be crucial to improve the sequence accuracy for some colonial hydrozoans.